The Temporal Impact of Prosthesis Implantation and Semi‐Quantitative Criteria on the Diagnostic Efficacy of Triple‐Phase Bone Scanning for Periprosthetic Joint Infection. Issue 7 (14th June 2022) - Zhang, Feiyang; Shen, Chentian; Yu, Jinlong; Chen, Xiaohua; Wang, Qiaojie; Sun, Zhenkui; Shen, Hao
Abstract : Objective: To evaluate the diagnostic efficacy of triple‐phase bone scanning and the temporal impact of prosthesis implantation on the diagnostic efficacy of triple‐phase bone scanning for periprosthetic joint infection (PJI). Methods: Patients who were admitted to our hospital for joint pain and dysfunction after total joint arthroplasty between 2014 and 2020 were retrospectively included. Triple‐phase bone scanning was performed, and the blood pool images were evaluated to obtain the semi‐quantitative criteria. The patients were then grouped into six groups according to the time interval from index primary arthroplasty to triple‐phase bone scanning. We examined whether there were significant differences in sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and accuracy between the groups. Results: Overall, 66 patients who underwent total hip arthroplasty (THA) and 74 patients who underwent total knee arthroplasty (TKA) were analyzed. No significant differences were observed between visual analysis and semi‐quantitative measurement in terms of sensitivity, specificity, PPV, NPV, and accuracy. For patients with a time interval from prosthesis implantation to bone scanning of >1 year, visual analysis had a higher PPV (100%) in patients who underwent THA and the use of semi‐quantitative criteria had a higher NPV (85.7%) in patients who underwent TKA. Conclusion: The semi‐quantitative criteria showed no advantages in the diagnosis of PJI. In addition, triple‐phase bone scanning demonstrated good clinical diagnostic efficacy when the time interval from prosthesis implantation to bone scanning was >1 year. Abstract : In this work, we determined the semi‐quantitative criteria of triple‐phase bone scanning and evaluated the diagnostic efficacy of semi‐quantitative criteria and visual analysis for PJI. Clarifying the temporal impact of prosthesis implantation on the diagnostic efficacy of triple‐phase bone scanning for PJI.